Utilização de modelos matemáticos aplicados a situações do meio oeste catarinense - Camargo, Adenir dos Santos (2016)
In this task we show data of a research fulfilled with math teachers in the Midwest of Santa Catarina, this search helped to determine the mainly goal of this thesis,which presents a series of contextualized problems and some problems of Mathematical Modeling inspired and or motivated by issues linked to the region. Topics like the araucaria of Vˆanio Czerniak, the trusses bridges of the Contestado region, the growth of the population of capybaras and the weight gain of chickens as a function of age, besides that we brought a collection of problems at the end of each chapter with proposal of statement and letting the solution for the creativity and knowledge of each reader.